Cooperative cathodes for enhanced hexavalent chromium reduction and electricity generation in bioelectrochemical reactor with simultaneous sludge degradation - Yu, Hang; Cao, Yuhui; Zhao, Qingliang; Liang, Zhuyuan; Zhu, Yimin (Frontiers in Environmental Science, 2022)
A novel bioelectrochemical reactor assembled with cooperative cathodes of chemical cathode and bio-cathode (BERCC) and with excess sludge as the anodic substrate obtained continuous and effective of Cr(VI) reduction. Cooperative cathodes in BERCC stimulated the growth of electrochemically active microorganisms such as Geobacter sp. and Shewanella sp. in the anodic biofilm and produced 8.21±0.64 mg Coulomb/(L·h) more electrons than dual chemical cathodes in the bioelectrochemical reactor with dual chemical cathodes, which enhanced the electrons for electricity generation and Cr(VI) reduction by approximately 58.3% and 56.1±5.6%, respectively.